2005
DOI: 10.1111/j.1432-2277.2004.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

What can be learned from brain-death models?

Abstract: Summary Brain death of the donor is an important risk factor influencing graft outcome. In addition to its nonspecific effects, it potentiates graft immunogenicity and increases host alloresponsiveness. Thus brain death in addition to other unspecific injuries such as organ procurement, preservation and consequences of ischemia/reperfusion injury, contributes towards the change of an inert organ to an immunological altered graft. Prior to engraftment, brain death initiates a cascade of molecular and cellular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 52 publications
1
53
0
5
Order By: Relevance
“…These events are linked to ischemia after organ procurement and upregulation of inflammatory genes occurring as a result of brain death of the donor (25,32). The heparin coating protects the affected cells from the innate immune response of the blood.…”
Section: Discussionmentioning
confidence: 99%
“…These events are linked to ischemia after organ procurement and upregulation of inflammatory genes occurring as a result of brain death of the donor (25,32). The heparin coating protects the affected cells from the innate immune response of the blood.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence to show that non‐allo‐immunological factors including BD and ischemia reperfusion injury (IRI) play a crucial role in impaired short‐ but, even more importantly, in long‐term graft survival rates 7, 8, 9. The occurrence of BD is linked to hemodynamic fluctuations, organ hypoperfusion, hypothermia, coagulopathy, hormone depletion, and electrolyte abnormalities 10. In this context, donor BD has been shown to provoke increased expression of pro‐inflammatory cytokines, endothelial activation, increased expression of MHC class II molecules, infiltration of the donor organ with immune cells, and activation of the complement system 11.…”
Section: Introductionmentioning
confidence: 99%
“…MHC may increase graft immunogenicity via the T-cell recognition process. 58 In the pig, Skrabal et al 49 found an organspecific regulation of proinflammatory molecules in the kidney, heart, and lung following brain death. Of the cytokines and cytokine-related molecules measured, IL-1b and IL-6 increased in all organs whereas TNF-a only increased in lung tissue.…”
Section: Inflammatory and Immunological Aspects Of Brain Deathmentioning
confidence: 99%
“…63 In summary, brain death is associated with the release of proinflammatory substances and inflammatory responses are detected in all organs suitable for transplantation leading to immunologically activated organs before engraftment, resulting in histological damage, decreased function, and lower graft survival compared with organs from living donors. 58,[64][65][66][67][68] …”
Section: Inflammatory and Immunological Aspects Of Brain Deathmentioning
confidence: 99%